2020
DOI: 10.1039/d0cp04775a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the highly effective peptide bond hydrolysis by MOF-808 catalyst under biologically relevant conditions

Abstract: Efficient and selective hydrolysis of inert peptide bonds is of paramount importance. MOF-808, a metal-organic framework based on Zr6 nodes, can hydrolyze peptide bonds efficiently under biologically relevant conditions. However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 66 publications
8
33
0
Order By: Relevance
“…Previous DFT calculations have shown that GG binds the Zr 6 O 8 cluster preferably in a bidentate manner, bridging two metal ions in one cluster and activating the carbonyl group for nucleophilic attack of a water molecule. 62 The higher activity of Ce 6 compared to the Zr 6 cluster is consistent with the superior reactivity previously reported for Ce(IV) compared to Zr(IV) salts in peptide bond hydrolysis. 27 The reasons for the lower reactivity of CeZr 5 clusters are however still unclear and might be related to less preferred peptide coordination to two different metal centra, resulting in the decrease in the reaction rate.…”
Section: Articlesupporting
confidence: 87%
“…Previous DFT calculations have shown that GG binds the Zr 6 O 8 cluster preferably in a bidentate manner, bridging two metal ions in one cluster and activating the carbonyl group for nucleophilic attack of a water molecule. 62 The higher activity of Ce 6 compared to the Zr 6 cluster is consistent with the superior reactivity previously reported for Ce(IV) compared to Zr(IV) salts in peptide bond hydrolysis. 27 The reasons for the lower reactivity of CeZr 5 clusters are however still unclear and might be related to less preferred peptide coordination to two different metal centra, resulting in the decrease in the reaction rate.…”
Section: Articlesupporting
confidence: 87%
“…This hypothesis is fully in line with our recent mechanistic studies. 38 The temperature also exerted a strong effect on the observed reaction rate, and calculation of activation parameters evidenced a large entropic contribution to the energy barrier, as observed before for the NU-1000 topology in these reactions. 20 The activity of Hf-NU-1000 was strongly affected by an increase in the reaction temperature with nearly 20-fold reduction to the half-life from 990 hours at 40 °C to 51 hours at 80 °C.…”
Section: Hydrolytic Activity Of Hf-nu-1000 Toward Peptide Bond Hydrolysissupporting
confidence: 68%
“…Notably, in this range the carboxylate group of GG is deprotonated, allowing for an efficient substrate-metal node interaction and a swift deprotonation of the entering water molecule. Such mechanism has been previously theoretically predicted for an analogous Zr-MOF, 38 and could explain the higher activity in mildly alkaline solutions. The observed lower adsorptions of GG at lower pH values indicates that the substrate-material interaction is less efficient, which is consistent with the lower rates observed in mildly acidic solutions (Figure S3).…”
Section: Hydrolytic Activity Of Hf-nu-1000 Toward Peptide Bond Hydrolysissupporting
confidence: 60%
“…Balancing the loss of Zn II -OSO 3 connectivity,t here is an increase in Ce-monomer-sulfate bonding (Table S10). S4), crystallizes in the triclinic P " 1space group (V = 16 197 3 ). An isomorphic Cu-analogue was also obtained, but only the Ni structure will be discussed here.Asthe main feature of all the U 70 and Ce 70 frameworks,t he rings are offset stacked along the a-axis (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%